Combined effect of transcutaneous auricular vagus nerve stimulation and 0.1 Hz slow-paced breathing on working memory - Tian, Qian-Qian; Cheng, Chen; Liu, Peng-Hui; Yin, Zi-Xin; Zhang, Meng-Kai; Cui, Ya-Peng; Zhao, Rui; Deng, Hui; Lu, Li-Ming; Tang, Chun-Zhi; Xu, Neng-Gui; Yang, Xue-Juan; et al. (Frontiers in Neuroscience, 2023)
Background: Previous research has found that transcutaneous auricular vagus nerve stimulation (taVNS) can improve working memory (WM) performance. In addition, 0.1 Hz slow-paced breathing (SPB, i.e., breathe at about 6 breaths/min) can significantly influence’ physical state and cognitive functions via changes in autonomic afferent activity. In the present study, we investigated the synergistic effects of taVNS and SPB on WM performance. Method: A total of 96 healthy people participated in this within-subjects experiment involving four conditions, namely taVNS, SPB, combined taVNS with SPB (taVNS+SPB), and sham. Each participant underwent these interventions for 30-min and WM was compared pre- and post-intervention using the spatial and digit n-back tasks in a random order four times. Permutation-based analysis of variance was used to test the interaction between time and interventions. Results: For the spatial 3-back task, there was a significant interaction between time and stimulation in the accuracy rate of matching trials (mACC, p =.03). Post-hoc analysis suggested that both taVNS and taVNS+SPB intervention improved participants’ WM performance; however, no significant difference was found in SPB or sham groups. Conclusions: This study has replicated the effects of taVNS on WM performance found in previous studies; however, the synergistic effects of combined taVNS and SPB required further research.